NAMÛDZAJ TATHWÎR MAWÂD TA’LÎM AL-LUGHAH AL-‘ARABIYAH FÎ DHAU AL-TAKÂMULI BAINA AL-‘ILMI WA AL-WAHYI - Siti Sanah; M Abdul Hamid (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2020)
The aims of the article to develop Arabic language teaching materials based on the complementarity between science and relevation for students of the Department of Mathematics and Science. This research used the research and development approach using Dick and Carey's development model that was modified by Lawrence Cunning Ham. The method to obtain the data used in this research is observation, questionnaire, interview and test. The educational material development model has been modeled in light of the complementarity between science and revelation, evident in two places: Firstly, in defining the educational objectives and educational outcomes that include attitudes, knowledge and skills, and secondly in defining the teaching materials related to mathematics and the natural sciences, and for those subjects and Hay Dal (Qur’anic verses) in them. The development model in this research is called Teaching Arabic for Special Purposes. The results of the research are evident from all the results of students in the four academic divisions in education, which indicate a high rate of over 0.70 (70%).